Customizing English Language Teaching to Suit Individual Learning Styles of Students - Gonzalo Guamán Condoy, Erich (ESPOCH Congresses: The Ecuadorian Journal of S.T.E.A.M., 2024)
This article explores the importance of understanding individual learning styles in the context of English language instruction for students. It argues that tailoring instructional methods and materials, to match the learning preferences of each student can enhance their overall learning experience and lead to better outcomes. The article reviews different learning styles and presents strategies for identifying them through assessment tools. It then discusses specific techniques and activities that can be used to target each learning style, including visual, auditory, kinesthetic, and tactile approaches. The article concludes by emphasizing the importance of flexibility and creativity in instructional design to meet the diverse needs of students. Keywords: learning styles, English language instruction, individual needs, instructional design, assessment, visual, auditory, kinesthetic